Haematological abnormalities in children with sickle cell disease and non-severe malaria infection in western Kenya - Kosiyo, Paul (BMC Infect Dis, 2021)
BACKGROUND: In Plasmodium falciparum infection, clinical conditions such as anaemia, thrombocytopenia and leukocytosis are common. Mutation in haemoglobin sub-unit beta gene (HBB) may be a genetic factor responsible for these haematological changes during infection. However, the contributions of the carriage of different HBB genotypes on these changes remain largely unknown. METHODOLOGY: In this cross-sectional study, we evaluated haematological abnormalities in P. falciparum-infected children (n = 217, aged 1–192 months) with different haemoglobin sub-unit beta (HBB) genotypes (HbAA, HbAS and HbSS). Children with acute febrile conditions were recruited at Jaramogi Oginga Odinga Teaching and Referral Hospital at the outpatient clinic. Haematological parameters were determined using Beckman Coulter counter ACTdiff2™ while HBB genotyping was done using TaqMan® SNP genotyping assay. Chi-square (χ(2)) was used to determine differences between proportions. Differences in haematological parameters were compared across groups using Kruskal Wallis test and between groups using Mann Whitney U test. Partial correlation test was used to determine correlation between haematological parameters and sickle cell genotypes while controlling for age and sex. RESULTS: Haemoglobin (Hb), [median (IQR); 7.3 (1.3), P = 0.001], haematocrit (HCT), [median (IQR); 26.4 (4.4), P = 0.009], red blood cells (RBC), [median (IQR); 3.2 (1.7), P = 0.048] were markedly reduced in HbSS, however, red cell distribution with (RDW) [median (IQR); 14.9 (3.3), P = 0.030] was increased in malaria infected children with HbSS. Severe anaemia was highest in HbSS (23.1%) followed by HbAA (8.6%) and HbAS (7.1%). There were no differences in platelet count (P = 0.399) hence no severe thrombocytopeania across the genotypes. Leukocytosis was highest in HbSS (69.2%), 42% in HbAS and 31% in HbAA. The RBC, HCT and Hb had negative correlation with RDW in HbSS in malarial-infected children (r = − 0.725, P = 0.008), (r = − 0.718, P = 0.009) and (r = − 0.792, P = 0.002), respectively. CONCLUSION: Our study reveals that anaemia is the most common abnormality in malaria-infected children with carriage of HbSS. The RBC, HCT and Hb concentration decrease with increase in RDW levels in infected children with carriage of HbSS compared to other HBB genotypes. Therefore, carriage of HbSS genotype is correlated with severity of haematological abnormalities. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12879-021-06025-7.